Smart Key Based Locker Desıgn Wıth Arduıno - Stefanus Eko Prasetyo; Jonathan Felix Andrianto (Universitas Internasional Batam, 2021)
A locker is a small cupboard that functions as a temporary storage area for items such as bags, wallets, and others. Lockers are widely used, especially in public places such as swimming pools, tourist attractions, and even factories where we are not allowed to carry goods for safety and security reasons. Unfortunately, there is one drawback of lockers, namely the locking feature still uses keys in general which are prone to loss. To reduce the risk of loss, this research was conducted to implement an IoT (Internet of Things) system on a locker using the “Blynk” application and Arduino media devices to control the locker without having to fear losing keys (Doshi et al., 2017)